Healthcare resource utilisation and costs in infants with confirmed respiratory syncytial virus infections: a national population cohort study - Hyun Jin Han; Dahye Ryu; Ju Young Kim; Semin Jang; Hae Sun Suh (BMC Infectious Diseases)
Abstract Background Respiratory syncytial virus (RSV) is the leading cause of severe respiratory infections in infants worldwide, significantly affecting their health and contributing to the global healthcare burden. We aimed to examine healthcare resource utilisation patterns and costs for infants under one year old with confirmed RSV infection across subgroups of different gestational ages and health conditions and the cost implications of RSV infections over time, thereby demonstrating the economic burden of the disease. Methods This retrospective cohort study utilised nationwide claims data from the Korea Health Insurance Review and Assessment Service for infants under one year of age with confirmed RSV infection in the first year of life from January 2017 to April 2022. The infants were stratified into three subgroups based on their gestational age and health status: unhealthy preterm, healthy preterm, and full-term infants. A descriptive analysis was conducted to estimate healthcare utilization by type of resource and costs related to the treatment of RSV. Results Out of 93,585 RSV infections identified, 31,206 patients met the inclusion criteria; these included 963 unhealthy preterm, 1,768 healthy preterm and 28,475 full-term infants. In our study, 76.3% of the infants with confirmed RSV infection required intensive care, including hospitalisation and more critical interventions such as intensive care unit (ICU) or mechanical ventilation (MV). The total average cost of RSV management was notably higher for unhealthy preterm infants ($ 6,325; 95% confidence interval (CI): $ 5,484-7,165) than for healthy preterm ($ 1,134; 95% CI: $ 1,006 − 1,261) and full-term infants ($ 606; 95% CI: 583–630). Our findings confirmed a significant epidemiological and economic burden, with infants at greater risk–shorter gestational age and poorer health conditions. Furthermore, we observed a marked increase in the total average cost of RSV management during COVID-19, reflecting the complex interplay between RSV and pandemic-related healthcare dynamics. Conclusion Our findings provide evidence for the significant economic burden of RSV infection among infants, with considerable disparities based on gestational age and health status subgroups. However, RSV prevention policies should also recognise that healthy preterm or full-term infants who receive intensive care face a significant disease burden.